Expansile Traumatic Neuroma of the Intratemporal Facial Nerve - Feng, Yening (J Neurol Surg Rep, 2019)
Objectives  To present a rare case of traumatic facial neuroma involving the geniculate ganglion and review relevant literature. Patient  Thirty-year-old man. Intervention  Microsurgical resection via combined mastoid-middle fossa approach with great auricular nerve interpositional graft. Main Outcome Measures  Patient demographics and pre- and postoperative facial nerve function. Results  A 30-year-old man with a reported history of prior Bell's palsy developed progressive complete (House–Brackmann VI) right facial paralysis following blunt trauma. Imaging was strongly suggestive of a geniculate ganglion hemangioma. As the patient had no spontaneous improvement in his poor facial function over the course of 9 months, he underwent resection of the facial nerve lesion with great auricular nerve graft interposition via a combined mastoid-middle fossa approach. Histopathology demonstrated disorganized fascicles, with axonal clustering reminiscent of sprouting/regeneration following trauma. No cellular proliferation or vascular malformation was present. Conclusion  Traumatic facial nerve neuromas can occur following temporal bone trauma and can closely mimic primary facial nerve tumors. Akin to the management of geniculate ganglion hemangioma and schwannoma, preoperative facial function largely dictates if and when surgery should be pursued.